2017
DOI: 10.1590/1678-457x.20016
|View full text |Cite
|
Sign up to set email alerts
|

Effects of CO2 pretreatment on the volatile compounds of dried Chinese jujube (Zizyphus jujuba Miller)

Abstract: The aim of this study was to investigate whether anaerobic metabolites could induce volatile compounds and improve aroma of dried jujube (Ziziphus jujuba Miller). Jujube fruits were incubated in a polyvinyl chloride bag containing 5% CO 2 and 95% N 2 for up to 168 h at 25 °C and 3 samples were randomly removed every 6 h and oven dried to a moisture content of ≅ 20%. The volatile compounds of control and 5% CO 2 -pretreated Chinese jujube fruits were extracted by simultaneous distillation extraction and identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Chen et al reported that acids were the major group among all the volatile chemicals in dried jujube fruits. Moreover, pre-treatment of jujube fruits with 5% CO 2 can induce a decrease in acid content during drying, which is mainly caused by a decrease in lauric acid and nutmeg acid content [18]. 2-Methoxy-4-cresol was a newly detected component in the VOCs of jujube fruits, which appeared with high content in fresh DZ but not found in fresh JS and showed a pleasant clove-like flavor [50].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chen et al reported that acids were the major group among all the volatile chemicals in dried jujube fruits. Moreover, pre-treatment of jujube fruits with 5% CO 2 can induce a decrease in acid content during drying, which is mainly caused by a decrease in lauric acid and nutmeg acid content [18]. 2-Methoxy-4-cresol was a newly detected component in the VOCs of jujube fruits, which appeared with high content in fresh DZ but not found in fresh JS and showed a pleasant clove-like flavor [50].…”
Section: Resultsmentioning
confidence: 99%
“…Aroma profiles are important characteristics to evaluate the quality of fruits. Several studies have reported that the volatile compounds of jujube fruits are affected by many factors, such as growth period [14], extraction methods [15], the load [16], and processing methods [17,18,19,20]. However, few reports have been associated with changes in volatile compounds of jujube fruits during cold storage, which should be considered.…”
Section: Introductionmentioning
confidence: 99%
“…However, its content in other cultivars was lower than that of n-decanoic acid. Besides, it is worthy of mention that the acids was reported to be the major group among all the volatile chemicals in dried jujube (Chen et al 2017).…”
Section: Identification and Quantification Of Volatile Compounds By Gmentioning
confidence: 99%
“…Xinjiang is an important jujube production region in China and its annual yield has significantly increased since 2010 (Jin et al, 2015). Ot has been reported that the Xinjiang region has a total 483,628 hectares jujube planting area, which can result in a more than 2.5 million tons annual production on the fresh jujube fruits (Chen et al, 2017). Geographically, Xinjiang is in the northwest of China, and it possesses a high day-to-night temperature difference.…”
Section: Introductionmentioning
confidence: 99%